2020
DOI: 10.1111/mec.15470
|View full text |Cite
|
Sign up to set email alerts
|

How do microbiota associated with an invasive seaweed vary across scales?

Abstract: Communities are shaped by scale dependent processes. To study the diversity and variation of microbial communities across scales, the invasive and widespread seaweed Agarophyton vermiculophyllum presents a unique opportunity. We characterized pro‐ and eukaryotic communities associated with this holobiont across its known distribution range, which stretches over the northern hemisphere. Our data reveal that community composition and diversity in the holobiont vary at local but also larger geographic scales. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(87 citation statements)
references
References 82 publications
4
83
0
Order By: Relevance
“…Algae were sampled from August 27 th to September 21 st (2017) from seven populations also collected for Bonthond et al [ 28 ], including three native populations; Akkeshi (Japan), Soukanzan (Japan), Rongcheng (China); and four non-native populations; Pleudihen-sur-Rance (France), Nordstrand (Germany), Cape Charles Beach (Viriginia) and Tomales Bay (California, Fig. 1 , Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Algae were sampled from August 27 th to September 21 st (2017) from seven populations also collected for Bonthond et al [ 28 ], including three native populations; Akkeshi (Japan), Soukanzan (Japan), Rongcheng (China); and four non-native populations; Pleudihen-sur-Rance (France), Nordstrand (Germany), Cape Charles Beach (Viriginia) and Tomales Bay (California, Fig. 1 , Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, both groups received new ASW with 2 mL PES weekly and individuals treated with antibiotics received also 2 mL inoculum. The inoculum was prepared from individuals of all 7 populations, following the procedure to remove epibiota as described in Bonthond et al [ 28 ]. Briefly, apical fragments of 1 g were separated from the thallus and transferred to 50 mL tubes containing 15 ± 1 glass beads (3 mm) and 15 mL ASW and vortexed for 6 min to separate epibiota from the algal tissue.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2017b, Bonthond et al. 2020). In addition, recent studies have demonstrated the necessity of understanding the evolutionary ecology of haplodiplontic life cycles in the context of biological invasions (Lees et al.…”
Section: Figmentioning
confidence: 99%